Health Literacy Among Pacific Mothers in New Zealand: Exploring the Associations of Demographic and Behavioural Factors With Health Literacy of Pacific Mothers in the Context of Pacific Health and Well-being. - Sa'uLilo, Losi (Auckland University of Technology, 2016)
The physical and social factors related to non-communicable diseases (NCDs), including obesity, noninsulin-dependent diabetes mellitus or type 2 diabetes, ischemic heart disease, stroke, metabolic syndrome and some cancers, are multifaceted and complex (Ministry of Health [MoH], 2012a, 2012b, 2012c). One factor that may contribute to the inequitable burden of NCDs in Pacific people is health literacy; almost 90% of Pacific males and females aged 15 years and over have low health literacy (MoH, 2012c; University of Otago, & Ministry of Health, 2011). Health literacy is the ability to access, read, understand and interpret basic health related information to make informed health decisions to improve health outcomes (Kickbusch, Maag & Saan, 2005). Individuals with low health literacy are less likely to manage ill health including type 2 diabetes (Harris, 2000; Kim, Love, Quistberg & Shea, 2004), seek professional medical assistance (World Health Organisation [WHO], 2013), or interpret nutrition related information (U.S. Department of Health and Human Services, 2005). To date, there is no evidence to show that health literacy is related to NCDs among Pacific people in New Zealand. Further, no studies showing any associations between health literacy and health outcomes with Pacific mothers in New Zealand have been published. Using both qualitative and quantitative research methodology, this research examined the extent to which health literacy and health outcomes are related in Pacific mothers in New Zealand. In doing so, this research comprised two studies: firstly a quantitative study to determine the association(s) between the single item literacy screener and weight status in Pacific mothers; and secondly a qualitative study using focus groups with Pacific mothers and semi structured interviews with health professionals in New Zealand to: 1) determine whether public health information is being appropriately interpreted by Pacific mothers and 2a) explore and discuss the experiences of health professionals with Pacific mothers and their health issues and 2b) examine best practice for these health professionals in addressing potential health literacy issues for Pacific mothers in New Zealand.
Keywords: non communicable disease; health literacy; pacific mothers; behavioural factors; demographic factors; pacific health and well being; pacific health professionals